UJARAN KEBENCIAN DI ERA DIGITAL (PERSPEKTIF ETIKA KOMUNIKASI AL-QUR’AN DAN SOLUSINYA) - Lubis, Yasser Muda (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Communication ethics is an important aspect of social life. The Qur'an as a guide to life for Muslims contains relevant ethics to prevent and overcome hate speech, especially in the digital era. Hateful speech can cause very detrimental social divisions and conflicts. Therefore, it is important to understand how the Qur'an regulates communication ethics in order to create social harmony. This research uses a qualitative approach with thematic interpretation method. The main data source comes from verses of the Koran relating to communication ethics. Data analysis was carried out by identifying and interpreting these verses in the context of handling hate speech in the digital era. In addition, literature reviews of various interpretations are used to enrich the analysis. The research results show that the Qur'an teaches communication ethics that prioritize the values of honesty, justice, politeness and wisdom. The verses that discuss the prohibition of slander, incitement and negative provocation show that hate speech is strictly prohibited in Islam. The Qur'an also emphasizes the importance of giving advice in a good way and having wise dialogue. Implementing communication ethics in the Al-Qur'an can be an effective solution in dealing with hate speech. With the communication ethics in the Koran, society can build a harmonious environment. This research is really needed so that people can better understand and apply these ethics in everyday life.